The Influence of Career Development and Competence on Employee Performance at the Regional Office of DJBC South Sulawesi - Multazam Prayudhi; Idayanti Nursyamsi; Julius Jilbert (International Journal of Social Science, Education, Communication and Economics (SINOMICS JOURNAL), 2023)
This inquiries about points to decide the impact of Career Advancement and Competence on Representative Execution at the Territorial Office of DJBC South Sulawesi. The populace of this think about comprises workers of the Territorial Office of DJBC South Sulawesi, and the test estimate utilized is 48 people employing an immersed test. The information collection was conducted through perception and surveys. The information investigation procedure utilized was numerous straight relapse examinations utilizing Factual Item and Benefit Arrangement (SPSS). The comes about of this ponder shows that both Career Advancement and Competence have a critical synchronous impact on representative execution. Besides, it was found that Career Improvement features a critical halfway impact on representative execution, whereas Competence too incorporates a critical halfway impact on worker execution.